Prospective study of maternal perception of decreased fetal movement in third trimester and evaluation of its correlation with perinatal compromise - Nandi, Nupur; Agarwal, Ritika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intrauterine fetal movements are sign of fetal life and well being. Perception of decreased fetal movements by the expecting mother is a common concern for both the mother and her obstetrician. Inadequate evaluation of reported decreased fetal movements may lead to catastrophic perinatal outcome. These necessitates us to identify the mothers perceiving decreased fetal movements, evaluating them to identify any risk factor, and follow up them to know the correlation with perinatal outcome. Methods: Antenatal mothers with singleton pregnancy at third trimester are recruited from OPD/ Emergency of Obstetrics and Gynaecology departments of Teerthankar Mahaveer Medical College and Research Center, Moradabad, Uttar Pradesh, India. Both case and control group comprise of 80 mothers matched by demographic profile, with perception of decreased fetal movements only in case group. They were evaluated thoroughly to identify risk factor if any and were followed up till delivery to know the perinatal outcome. Results: Majority of women reporting reduced fetal movements were between 20-30 years of age group (73%), Primigravida (80%), 72.5% were at term pregnancy. Common (46%) pattern of decreased movements was both in frequency and as well as intensity. 62% women with decreased fetal movements had anteriorly placed placenta. In the study group, 48.75% women were identified with risk factor, and association of more than one antenatal risk factor was significantly high (p value 0.0026). LBW was more common (21.25%), many neonates were associated with low Apgar score in the study group. Conclusions: Pregnant mothers reported with decreased fetal movement in third trimester should be evaluated adequately for identification of risk factors, as well as for fetal surveillance. Record of fetal movement for 2 hours while the mother is in rest, Cardiotocography, elaborative USG, BPP should be monitored to have good perinatal outcome by providing timely intervention.